HIGH STRENGTH MANGO LEAF WASTE/POLYURETHANE COMPOSITE REINFORCEMENT USING QUARTZ MATERIAL - Masturi, Masturi; Alighiri, Dante; Choirunnisa, Fadhillah; Kirana, Kurnia Galuh Candra (Spektra: Jurnal Fisika dan Aplikasinya, 2023)
Quartz stone contains silica components (SiO2) which have the ability as a reinforcement material for composite materials. Quartz SEM-EDX testing shows that the quartz silica comonent is 69%. Other components contained in quartz are 34% MgO and 2% CaO. Therefore, quartz stone is used as a reinforcing material in mango leaf waste composite materials. Meanwhile, compressive strength testing of composite materials was carried out with variations of Polyurethane (PU) polymers, namely 1, 2, 3, 4, 5, 6, and 7 grams, obtaining the highest maximum pressure at 6 grams polymer mass, which is 38.91 grams. Testing of composite materials that have been given a mixture of quartz stone with a mass of Polyurethane (PU) 6 grams and a quartz stone variation of 0.03; 0,06; 0,09; 0,12; 0,15; and 0.18 grams obtained the maximum power most optimally there is a quartz mass of 0.06 grams of 40.47 grams. The strength of mango leaf composite meets the strength standard for building materials, namely concrete with a value of 20-150 MPa. This shows that quartz stone can be a composite reinforcement comprehenent for mango leaf waste.